Bromine-Radical-Mediated Synthesis of β-Functionalized β,γ- and δ,ε-Unsaturated Ketones via C–H Functionalization of Aldehydes - Kippo, Takashi; Kimura, Yuki; Ueda, Mitsuhiro; Fukuyama, Takahide; Ryu, Ilhyong (Synlett, 2017)
The bromine-radical-mediated allylation reaction of aldehydes was studied. In the presence of V-65 as radical initiator, the reaction of aldehydes with allyl bromides gave β,γ-unsaturated ketones in good yields (13 examples, 45–84%). The reaction is triggered by hydrogen abstraction from the aldehyde by bromine radical to form an acyl radical, which undergoes an SH2′-type addition–elimination reaction with allyl bromides to give coupling products with liberation of bromine radical. Three-component coupling reactions comprising aldehydes, electron-deficient alkenes, and methallyl bromide also proceeded to give δ,ε-unsaturated ketones.
Keywords: bromine radical; SH2′ reaction; β,γ-unsaturated ketones; δ,ε-unsaturated ketones; three-component reaction